PENGARUH FAKTOR ESG (ENVIRONMENTAL, SOCIAL, AND GOVERNANCE) TERHADAP KINERJA SAHAM PERUSAHAAN - Fatia Hadaya Panjaitan; Siti Aulia Zannah; Ahmad Wahyudi Zein (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on corporate stock performance. ESG is understood as a sustainability approach that includes environmental, social, and governance aspects of a company. The research method used is a qualitative approach with a literature review based on scientific journals published between 2021 and 2026. The findings indicate that ESG plays an important role in increasing investor confidence by reducing risks, improving transparency, and strengthening corporate reputation. However, the impact of ESG on stock performance varies across sectors and market conditions. Overall, ESG contributes positively to long-term firm value and investment attractiveness.